The Analysis of Performance Measurement Using Levers of Organization Design Concept - Yessi Yunelia Rahmi (Politeknik Caltex Riau, 2016)
This research is case study in retail company which is PT Midi Utama Indonesia, Tbk Branch Bitung. In running retail business, company supported by all branches to give contribution in giving the best performance. Every branch include the employee inside will compete to achieve target that established by company. Branch Manager will evaluate performance for every employee. The manager need to understand about organization design in branch to avoid performance decreasing. Performance measurement in this research analyzed by Levers of Organization Design Concept.The result of this case study in PT Midi Utama Indonesia, Tbk Branch Bitung shows that company using Key Performance Indicator in measuring Manager performance. The current Key Performance Indicator of Branch Manager has been appropriate with span of control of Branch Manager. But, Key Performance Indicator of Distribution Center Manager, Area Manager, Area Coordinator has not been fully appropriate with span of control for every manager. Therefore, Distribution Center Manager, Area Manager, Area Coordinator need span of influence and span of support from another department to achieve branch target.